Screening and Identification of Cellulase- Producing Bacteria Isolated From Rumen of Camel in Sokoto Main Abattoir - H. M. Maiturare, Nafi’u. A.,M. H. Usman B. Y., Abdullahi , Mustapha G (International Journal of Scientific Research and Management (IJSRM), 2017)
Cellulose is the most abundant polymers on the earth and was extensively used for many industrial purposes. The aim of the study was screening and isolation of cellulase producing bacteria from rumen of camel in slaughter house of Sokoto. A numbers of rumen content samples were collected from four different camels for analysis. Rumen cellulase producing bacteria were Isolated and characterized in this experiment following serial dilution up to six fold and inoculated into Nutrient agar. Biochemical test such citrate utilization, indole, catalase, urease, methyl red, vogues proskauer, motility, and sugar fermentation, starch hydrolysis, hydrogen sulphide production (H2S) from triple sugar iron (TSI) agar and sugar fermentation were adopt in this study. Screening of the isolates was performed in an enriched media containing Carboxymethyl cellulose (CMC) flooded with Congo red and washed with NaCl. The result revealed the colonial characterization such as shape, color, size, elevation margin, opacity, and gram reaction were determined for each of the isolates. A total of seven isolates were identified, six were identified as gram positive while one as gram negative. Bergy’s manual of determinative bacteriology confirmed the isolates to be genus of Bacillus spp. The mean total count of bacteria are 2.5 x 106 cfu/g, 2.8 x 106 cfu/g, 3.5 x 106 cfu/g, 3.6 x 106 cfu/g, 2.7 x 106 cfu/g, 3.5 x 106 cfu/g and 3.0 x 106 cfu/g. Five out of seven show CMCase activity after flooding with Congo red and are considered as RC3, RC4, RC5, RC6, and RC7 while two isolates RC1 and RC2 lack ability to produce cellulase RC7 show highest ability to produce cellulase with highest diameter of 6.0 mm. It has concluded that rumen content of camel is good source of carbon sole and cellulase producing bacteria.